Board of Directors’ Surface Level Diversity and Innovation Performance - Belkacemi , Ramzi; Papadopoulos , Andrew; Bouzinab, Kamal (Journal of Leadership, Accountability and Ethics, 2021)
This paper seeks to study the potential impact of board of directors on innovation. It more specifically focuses on directors’ surface level diversity (gender, ethnic and age diversity) and innovation performance based on an international sample of 97 firms totalizing 1027 directors. As hypothesised, our approach revealed that gender diversity has a positive impact on innovation performance where cultural diversity has a negative influence. On its part, age diversity did not yield a significant result. However, we were also able to conclude of the relevance of having a board that is mainly comprised of independent members, as well as that of contingencies (firm size, region and sector), regarding innovation performance. Overall, our findings are consistent with the resource dependency perspective, robust after addressing some potential endogeneity issues, and contain various implications for both professionals and academics.